Laser-induced spin dynamics in the iron-yttrium garnet film doped with Si ions - S. V. Ovcharenko; M. S. Gaponov; N. A. Ilyin; M. V. Logunov; Anhua Wu; E. D. Mishina (Российский технологический журнал, 2020)
A continuous increase in the volume of stored and processed data leads to stricter requirements for storage media. The most common information storage technology is currently based on magnetic materials, where information in the form of "0" and "1" is associated with the local direction of magnetization, determined by the external magnetic field created by the recording device. It is known that this approach has fundamental limitations on the recording speed which is almost achieved. The requirements for energy efficiency of storage media are also being made stricter. These circumstances lead to the development of alternative approaches to recording information. One of these approaches has been demonstrated in the field of ultrafast opto-magnetism, which has been booming over the past 20 years. It consists in recording information with short optical pulses without the application of an external magnetic field. However, it requires fundamental studies of physical processes, as well as materials, in which magnetization can be controlled by short optical pulses. In this paper, we consider the spin dynamics in a magnetic dielectric: a film of iron - yttrium garnet doped with silicon. The studies were carried out using the pump – probe technique over a time range of up to 800 ns. The spot size was 30 μm, the optical pulse duration was 35 fs, and the pump fluence was about 50 mJ/cm2. It is shown that a change in the magnetocrystalline anisotropy constants due to the action of a pump pulse on the structure causes a long-decaying magnetization precession with a period of about 200 ps. The dependences of the amplitude, phase, and decay of the precession on the magnitude of the external magnetic field in the range up to 1.84 kOe were obtained and analyzed. The studied processes can be considered on the basis of the Landau-Lifshitz-Gilbert model, and be of interest for the optical switching of magnetization, as well as the creation of various spintronic devices. It is shown that films of iron-yttrium garnet doped with silicon are a promising material for magnetic information carriers based on ultrafast opto-magnetism.